2017
DOI: 10.1182/bloodadvances.2016001321
|View full text |Cite|
|
Sign up to set email alerts
|

The class I scavenger receptor CD163 promotes internalization of ADAMTS13 by macrophages

Abstract: Key Points• Uptake of ADAMTS13 by macrophages is not dependent on the macrophage mannose receptor.• CD163 promotes internalization of ADAMTS13 by macrophages.Internalization of ADAMTS13 by macrophages may contribute to its clearance from the circulation. Here we investigated endocytic mechanisms that contribute to the uptake of ADAMTS13 by macrophages. Human monocyte-derived macrophages were used to monitor the uptake of fluorescently labeled recombinant ADAMTS13 by flow cytometry.Internalization of ADAMTS13 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
(70 reference statements)
1
10
0
Order By: Relevance
“… 37 More recently, we described the involvement of CD163 in the internalization of ADAMTS13 by macrophages in vitro . 38 In the latter study, we observed that the uptake efficiency of CD163-positive macrophages was approximately 10 times higher when compared to that of mo-DCs (that are devoid of CD163 expression). Based on this finding, it is tempting to speculate that the limited presentation of ADAMTS13-derived peptides on mo-DCs is due to a relatively low efficiency to internalize ADAMTS13, thereby limiting the number of ADAMTS13-derived peptides that are presented.…”
Section: Discussionmentioning
confidence: 66%
“… 37 More recently, we described the involvement of CD163 in the internalization of ADAMTS13 by macrophages in vitro . 38 In the latter study, we observed that the uptake efficiency of CD163-positive macrophages was approximately 10 times higher when compared to that of mo-DCs (that are devoid of CD163 expression). Based on this finding, it is tempting to speculate that the limited presentation of ADAMTS13-derived peptides on mo-DCs is due to a relatively low efficiency to internalize ADAMTS13, thereby limiting the number of ADAMTS13-derived peptides that are presented.…”
Section: Discussionmentioning
confidence: 66%
“…sCD163 function is unclear, but it was shown to potentiate IL‐10 expression in allergen‐activated PBMCs 65 and to inhibit T cell activation/proliferation, 66 hence promoting inflammatory resolution. CD163 facilitates the hemoglobin‐haptoglobin complex 67 and ADAMTS13 68 internalization. Our analysis showed no direct binding between CD163 and α‐syn, regardless of calcium concentration, suggesting that α‐syn is not a direct ligand for CD163 (possible coreceptor interactions cannot be excluded).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sCD163 seems to inhibit T cell activation and proliferation [58]. It is known that CD163 is in charge of the uptake of the hemoglobin-haptoglobin complex [40] and ADAMTS13 [83]. In order to assess whether α-syn could be a cognate for CD163, we did MST to assess co-interaction.…”
Section: Discussionmentioning
confidence: 99%
“…sCD163 function is unclear, but it was shown to potentiate IL-10 expression in allergen-activated PBMCs 65 and to inhibit T cell activation/proliferation 66 , hence promoting inflammatory resolution. CD163 facilitates hemoglobin-haptoglobin complex 67 and ADAMTS13 68 internalization. Our analysis showed no direct binding between CD163 and α-syn, regardless of calcium concentration, suggesting that α-syn is not a direct ligand for CD163 (possible co-receptor interactions cannot be excluded).…”
Section: Discussionmentioning
confidence: 99%